Influence of surface treatments on the mechanical properties of fibre reinforced thermoplastic composites. (2017) - Bessa, João; Matos, Joana; Mota, Carlos; Cunha, Fernando; Araújo, Isabel; Silva, Luís; Pinho, Elizabete; Fangueiro, Raúl
Abstract: This work compares the effect of different types of surface treatments of natural fibrous materials, particularly flax, on the mechanical properties of thermoplastic polymer composites for application in automotive sector. The application of surface treatments on fibrous materials can improve the compatibility with polymeric materials. Different surface treatments were applied, namely: cleaning (L); alkali (A); coupling of different functional groups, such as benzoyl (B), amino (SA), epoxy (SE); corona (C). After the application of surface treatments, the fibrous materials were combined with polymeric materials, particularly thermoplastic polyolefin (TPO), by compression moulding. The mechanical tests were performed to evaluate the influence of different surface treatments on flax fabrics on the mechanical properties of TPO combined with these fibrous materials. The experimental results show that the surface treatments on the flax fabrics strongly affect the mechanical properties of the final composite materials, mainly breaking elongation and Young's modulus. Composite materials with flax fabrics subjected to a L+A and L+A+SE treatments show the lower values of Young's modulus corresponding to larger elongation values for the same load. For these set of treatments, the elongation was increased more of 100%, comparing to a composite material with flax fabric without any surface treatment. These results allow to conclude that the surface treatments can increase the elongation capacity of the flax fabrics reinforced TPO, without loss of mechanical properties.